New design of wideband microstrip branch line coupler using T-shape and open stub for 5G application - Ali Abdulateef Abdulbari; Sharul Kamal Abdul Rahim; Mohamad Zoinol Abidin Abd Aziz; K. G. Tan; N. K. Noordin; M. Z. M. Nor (Institute of Advanced Engineering and Science, 2021)
A new design of wideband branch-line coupler (BLC) using T-shape with open stub microstrip line is proposed. The branch line coupler is integrated with low and high impedance λ/4 transmission lines to achieve the comparatively compact size of (27.2 mm × 16.5 mm). operating the bandwidth in simulated of BLC from 2.9 to 4 GHz is obtained 30.22% with a frequency center of 3.5 GHz. Meanwhile, the measured bandwidth of the BLC is cover from 2.8 GHz to 4.22 GHz is equal 33.40% at the center frequency 3.55 GHz respectively. The BLC simulated has low isolation and high return loss of -29.28 dB and -30.69 dB at the center frequency 3.5 GHz.Whereas, the measured result has a simple difference in the return loss and isolation are -27.43dB and -24.46 dB at the frequency 3.55GHz respectively. This BLC design has a good coupling factor of -2.97 and insertion loss of -3.65 dB. Furthermore, it obtains an excellent amplitude and phases different between two output of ±0.1 and 93.6°±3.4° with high performance. There is a good agreement between the simulated result and the measured result. This branch line coupler design used for 5G applications for future wireless communication systems.